Hunting interacts with socio‐demographic predictors of human perceptions of urban coyotes. (23rd August 2019) - Drake, Michael D.; Peterson, M. Nils; Griffith, Emily H.; Olfenbuttel, Colleen; Moorman, Christopher E.; Deperno, Christopher S.
ABSTRACT: Recent research suggests hunting participation interacts with other variables (e.g., bird‐watching participation) to shape attitudes about wildlife. We build on this research by evaluating how hunting participation interacted with key variables to predict affectual attitudes toward coyotes ( Canis latrans ), support for coyotes on the landscape, and support for coyote management approaches in urban North Carolina, USA. We conducted surveys of urban hunters and nonhunting urban residents during 2015, and modeled relationships between respondent attributes and perceptions of coyotes. Among nonhunters, men liked coyotes more than women did, but the relationship was reversed among hunters. Similarly, men supported killing coyotes more than women did, but the difference was less pronounced among hunters. Pet owners liked coyotes and opposed killing coyotes more than non–pet owners did, but those differences disappeared among hunters. Having a rural background predicted lower tolerance for coyotes among hunters but not nonhunters. Finally, age was negatively related to support for lethal coyote management among hunters but positively related to support among nonhunters. Participation in hunting may moderate how socio‐demographic variables predict perceptions of coyotes and change or reverse previously described relationships between these variables and perceptions of wildlife. © 2019 The Wildlife Society. Abstract : The hunting community is deeply tied to wildlife conservation in the United States and their perceptions of carnivores are important for shaping management policy. In a survey of urban and non‐urban hunters, we detected several interactions between participation in hunting and other demographic categories on perceptions of coyotes, indicating that hunting may moderate how socio‐demographic variables predict wildlife perceptions.